The influence of inclusive leadership styles on the safety behaviors of new generation high altitude railway construction workers - Mo Junwen; Cui Libing (Scientific Reports)
Abstract Research on the impact of different leadership styles on safety behavior has been extensively conducted across various fields. However, few studies have investigated the relationship between inclusive leadership and safety behavior, particularly between inclusive leadership and safety behavior (safety participation and safety compliance) among the new generation of high-altitude railway construction workers. This study, based on social exchange theory, social cognitive theory, and organizational personification theory, explains the relationship between inclusive leadership and the safety behavior of high-altitude railway construction workers (safety participation and safety compliance) by using safety self-efficacy as a mediating variable and perceived organizational support as a moderating variable. To address common method bias, a multi-source and multi-stage data collection design was used, gathering 315 valid questionnaires from construction workers on 10 high-altitude railway construction projects, with hypothesis testing performed through regression analysis. The results indicate that inclusive leadership not only directly affects safety behavior (safety participation and safety compliance) but also that safety self-efficacy partially mediates the relationship between inclusive leadership and safety behavior (safety participation and safety compliance). Additionally, perceived organizational support not only enhances the positive impact of inclusive leadership on safety self-efficacy but also strengthens the positive effect of inclusive leadership on safety behavior (safety participation and safety compliance). These findings enrich the research on the correlation between leadership styles and safety behavior among the new generation of high-altitude railway construction workers, and provide new perspectives and approaches for preventing safety accidents in high-altitude railway construction.